The geography of Chinese science - Andersson, David Emanuel; Find, Søren; Gunessee, Saileshsingh; Matthiessen, Christian Wichmann (SAGE Publications, 2014)
Chinese scientific output has increased dramatically in recent years, but its internal spatial structure has received scant attention. Estimated gravity models of intercity scientific co-authorships show that there are two types of spatial political bias in China, apart from the expected mass and distance effects. Intercity co-authorships involving Beijing are more common than Beijing’s output volume and location would imply, and this Beijing bias is increasing over time. The second type of spatial political bias is greater intra-provincial collaboration than is accounted for by size and distance. The geography of Chinese science is thus not only monocentric as regards overall scientific output, but also exhibits unusually hierarchical collaboration patterns. Unlike in Europe and North America, national and regional capitals are becoming ever more important as scientific coordination centers.